2005
DOI: 10.4049/jimmunol.174.7.4019
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 Activates Telomerase and Minimizes Telomere Loss and May Preserve the Replicative Life Span of Memory CD8+ T Cells In Vitro

Abstract: The preservation of the replicative life span of memory CD8+ T cells is vital for long-term immune protection. Although IL-15 plays a key role in the homeostasis of memory CD8+ T cells, it is unknown whether IL-15 regulates the replicative life span of memory CD8+ T cells. In this study, we report an analysis of telomerase expression and telomere length in human memory phenotype CD8+ T cells maintained by IL-15 in vitro. We demonstrate that IL-15 is capable of activating telomerase in memory CD8+ T cells via J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 39 publications
0
56
0
Order By: Relevance
“…There is no consensus on the units that best represent telomerase activity. Units such as ''arbitrary units'' (13), ''percentages'' (9,14), ''absorbance ratios'' (15), ''relative activity'' (16), and undefined ''units'' or ''activity'' (17,18) have been used by various authors to describe telomerase activity. Our results are presented as Ct to allow for comparability with the original study reported by Wege et al (9).…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the units that best represent telomerase activity. Units such as ''arbitrary units'' (13), ''percentages'' (9,14), ''absorbance ratios'' (15), ''relative activity'' (16), and undefined ''units'' or ''activity'' (17,18) have been used by various authors to describe telomerase activity. Our results are presented as Ct to allow for comparability with the original study reported by Wege et al (9).…”
Section: Discussionmentioning
confidence: 99%
“…As an important T cell growth factor, IL-15 has been demonstrated to prolong the persistence of adoptively transferred cytotoxic T cells (CTLs) in vivo (Quintarelli et al, 2007). The major effects of IL-15 on T cells include (1) enhanced cytotoxic ability and proliferation of CTLs in vivo (Klebanoff et al, 2004), (2) activation of the telomerase and elongation of telomeres (Li et al, 2005), (3) ability to rescue tumor-tolerant T cells for use in adoptive immunotherapy (Teague et al, 2006), and (4) inhibition of activation-induced cell death of T cells (Marks-Konczalik et al, 2000). However, whether and how IL-15 treatment could enhance the anti-tumor activity of adoptively transferred CD4 + T cells in vivo is not resolved until now.…”
Section: Introductionmentioning
confidence: 99%
“…122 Considering CD8 C T cells, IL-15 has been shown to increase CD8 C memory T cell longevity by inducing telomerase activity through JAK3 and PI3K signaling pathways. 123,124 A further study, looking at both IL-7 and IL-15 showed an upregulation of na€ ıve CD8 C T cells when incubated with these cytokines, with a higher response seen with IL-15. 125 Stimulation of telomerase activity in immune cells makes these cytokines potentially harmful to administer in cancers such as leukemia, where there is already uncontrolled telomerase activity occurring in T cells.…”
Section: Underlying Mechanisms That Increase Immune Cell Longevitymentioning
confidence: 99%
“…Induces Apoptosis 107,108 Telomerase activation 122 Unconfirmed Unconfirmed IL- 15 Decrease apoptosis 136 Decrease apoptosis 130,131 Unconfirmed Telomerase activation [123][124][125] Decrease apoptosis 132 engineering of cells described here, that can be regulated by transfection with suicide genes such as those for herpes simplex virus thymidine kinase (TK) 140 or CD20 141 or the use of transfected extracellular FK506 binding domains with Caspase-9 signaling motifs to cause cell death upon treatment with FK506. 142 …”
Section: Il-21mentioning
confidence: 99%